2012
DOI: 10.1161/circep.111.969485
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Versus Manual Catheter Navigation for Ablation of Free Wall Accessory Pathways in Children

Abstract: Background-Transcatheter ablation of accessory pathway (AP)-mediated tachycardia is routinely performed in children.Little data exist regarding the use of magnetic navigation (MN) and its potential benefits for ablation of AP-mediated tachycardia in this population. Methods and Results-We performed a retrospective review of prospectively gathered data in children undergoing radiofrequency ablation at our institution since the installation of MN (Stereotaxis Inc, St. Louis, MO) in March 2009. The efficacy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…For cardiac catheterization, Kim et al found a reduced fluoroscopy time when using the CARTO XP system [70]. Most of the other studies used RMN in combination with EM tracking, focusing on RMN.…”
Section: Clinical Evidencementioning
confidence: 99%
“…For cardiac catheterization, Kim et al found a reduced fluoroscopy time when using the CARTO XP system [70]. Most of the other studies used RMN in combination with EM tracking, focusing on RMN.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Recurrence of arrhythmia and/or preexcitation on 12-lead ECG was observed only in 4% of cases in this group. Only one other study described long-term outcomes of RMN-guided AP ablation in children [9] , where fewer recurrences were observed, though this study had a significantly shorter follow-up duration and only included left free wall AP’s. Ablation of left free wall AP’s has a higher success rate compared to other locations, which is likely to be the explanation for the discrepancy with the current study’s findings [2] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, several small studies were conducted and reported first experiences with the mentioned techniques [2] , [3] , [8] , [9] , [11] , [16] , [17] . There are no large scale studies comparing ablation techniques in children, nor investigating long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…EAMs have been developed to guide cardiac catheter navigation during adult and pediatric ablation procedures reducing or even excluding fluoroscopy exposure, as was demonstrated for the first time in 2002 by Drago et al . Currently, such EAMs are not routinely used during pacemaker implants, but there are some experiences with pacemakers and defibrillators described in adults .…”
Section: Discussionmentioning
confidence: 99%
“…EAMs have been developed to guide cardiac catheter navigation during adult and pediatric ablation procedures 12,18,19 reducing or even excluding fluoroscopy exposure, as was demonstrated for the first time in 2002 by Drago et al 20 Currently, such EAMs are not routinely used during pacemaker implants, but there are some experiences with pacemakers and defibrillators described in adults. [2][3][4][5][6][7] The use of EAM in pediatric patients was first reported in a retrospective study by Silver et al 8 EAM reduced radiation exposure for patients (and physicians), and…”
Section: Eam-rvaps (Current Data) Fluoroscopy Guided-rvaps 17 P-valuementioning
confidence: 99%